REVIEW OF SECURE ACCESS TO A WEB RESOURCE USING MACHINE LEARNING METHODS - Korobeinikova, Tetiana; Kravchuk, Nazar (Sworld-Us Conference proceedings, 2023)
The article explores the increasing security threat in the global cyberspace. Measures for assessing information access risks considering individuals' responsibility are proposed. Special attention is given to safeguarding web servers from CSRF attacks an